Patterns of Non-injection Drug Use Associated with Injection Cessation among Street-Involved Youth in Vancouver, Canada - Lake, Stephanie (J Urban Health, 2018)
Although abstinence from drug use is often a key goal of youth substance use treatment, transitioning to less harmful routes and types of drug use is desirable from both a clinical and public health perspective. Despite this, little is known about the trajectories of youth who inject drugs including changes in patterns of non-injection drug use. The At-Risk Youth Study (ARYS) is a longitudinal cohort of street-involved youth who use drugs in Vancouver, Canada. We used linear growth curve modeling to compare changes in non-injection drug use among participants who ceased injecting drugs for at least one 6-month period between September 2005 and May 2015 to matched controls who continued injecting over the same period. Of 387 eligible participants, 173 (44.7%) reported ceasing drug injection at least once. Non-injection drug use occurred during 160 (79.6%) periods of injection cessation. In adjusted linear growth curve analyses, the only non-injection drug use pattern observed to decrease significantly more than controls following injection cessation was daily crack/cocaine use (p = 0.024). With the exception of frequent crack/cocaine use, transitions out of injection drug use did not appear to coincide with increased reductions in patterns of non-injection drug use. Our findings indicate that most (80%) of the observed injection cessation events occurred in the context of ongoing substance use. Given that transitioning out of drug injection represents a significant reduction in risk and harm, efforts supporting vulnerable youth to move away from injecting may benefit from approaches that allow for ongoing non-injection drug use.